'The way we do the things we do' – decision making transparency at the Journal of Child Psychology and Psychiatry. (13th December 2017) - Sonuga‐Barke, Edmund J.S.
Abstract : As in life generally, so in scholarly publishing, the turn of the year inevitably encourages editors to reflect soberly and take honest stock of the progress their journals have made over the previous 12 months. In this frame of mind, my own thoughts turned to our beloved Journal of Child Psychology and Psychiatry. Of course I say ours because we who currently work at the journal, know it actually belongs to you, the world‐wide community of child and adolescent psychologists and psychiatrists: We are only its stewards. We hold it in trust for the whole field. We understand the important role that it has served, in shaping the field of scientific child psychology and psychiatry. We know it has a special place in both your intellectual and working lives. We are aware how important it is to you that the journal continues, on your behalf, to help drive the promotion of science‐driven and evidence‐based solutions to the great, and, in some aspects, growing, burden of suffering imposed by childhood mental and neuro‐developmental disorders. It is vital that we have your confidence that we do this in a transparent and fair way – without fear or favour – not letting our own preconceptions, prejudices or vested interests influence the content of what we publish – unless it is our prejudice towards, and vested interest in, finding out 'the truth of the matter'. We are acutely aware of the responsibility that all this places on our shoulders – a yoke we feel privileged to bear.